The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9ra06213k
|View full text |Cite
|
Sign up to set email alerts
|

Durable, acid-resistant copolymers from industrial by-product sulfur and microbially-produced tyrosine

Abstract: Copolymers of waste sulfur and bacterially-produced tyrosine are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
(48 reference statements)
0
36
0
Order By: Relevance
“…Although elemental sulfur itself is quite brittle, durable materials can be obtained for the copolymers comprising up to 90 wt.% sulfur [51][52][53][54]. These efforts have employed a wide range of starting materials including cellulose, lignin, amino acids, terpenoids, algae acids, polystyrene derivatives, and other olefins [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. More recently, radical-induced aryl halide/sulfur polymerization (RASP) proved similarly effective for preparation of high sulfur-content materials (HSMs) but employing aryl halides in place of the olefins required for inverse vulcanization.…”
Section: Lignin In High Sulfur-content Materialsmentioning
confidence: 99%
“…Although elemental sulfur itself is quite brittle, durable materials can be obtained for the copolymers comprising up to 90 wt.% sulfur [51][52][53][54]. These efforts have employed a wide range of starting materials including cellulose, lignin, amino acids, terpenoids, algae acids, polystyrene derivatives, and other olefins [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70]. More recently, radical-induced aryl halide/sulfur polymerization (RASP) proved similarly effective for preparation of high sulfur-content materials (HSMs) but employing aryl halides in place of the olefins required for inverse vulcanization.…”
Section: Lignin In High Sulfur-content Materialsmentioning
confidence: 99%
“…High sulfur-content materials (HSMs) can be conveniently prepared by the reaction of elemental sulfur with olefins by inverse vulcanization (InV) [1][2][3] or from aryl halides by radical-induced aryl halide-sulfur polymerization (RASP, Scheme 1). [4][5][6] HSMs produced by these routes have been proposed for applications such as electrode materials, [7][8][9][10][11][12] lenses for thermal imaging, [13] fertilizers [14,15] absorbents for removing toxins from water, [16][17][18][19][20][21] or as structural materials [22][23][24][25][26][27][28][29] and thermal insulators. [30,31] The InV mechanism proceeds when olefins are crosslinked by their reaction with sulfur radicals produced by heating elemental sulfur to >159 C. RASP involves thermal reaction of aryl halides with elemental sulfur whereby S C aryl bonds are formed, a process requiring slightly higher temperatures of 220-250 C.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is likely attributable to the presence of linolenic acid, a triply unsaturated fatty acid, in the technical‐grade sample, thus providing increased crosslink density in the ZLS x samples. Although linolenic acid is a minor component (~1%), it has been demonstrated that even 1% of a monounsaturated crosslinking agent can increase the T d of a composite by 20–40°C …”
Section: Resultsmentioning
confidence: 99%
“…The lower wt % sulfur composites ( ZPLS 85 and below and ZLS 90 and below) were not remeltable due to the increased crosslinking, and thus were not able to be cast into molds for DMA analysis. As the wt % of sulfur in the composites decreases, the storage modulus increases, as the higher percentage of organic material in the composite contains a higher number of double bonds and can stabilize the chains of sulfur crosslinking the material …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation